Lietuvos komjaunimo spaudos leidimas TSRS (1919–1940.VI) - Zaveckienė, Žiedūnė (Knygotyra, 1983)
In general the Lithuanian Komsomol Press publications are of great importance in the history of publication. After the defeat of the revoliution the so called white terror made the press be transfered to a foreign country. A great number of press leaders moved abroad as well.The Lithuanian Komsomol Press of 1919–1928 was published in Moscow, Smolensk, Minsk, Vitebsk.Twenty booklets were issued (about one third of all the publications in 1919-June, 1940). Some newspapers has been published as well but its share comparing with the other publications was rather small (5 of 81 publications). One of the most important publication of that period was “The Working Youth” issued in Smolensk. Here the greatest number of its was issues (36 of 51 copies).The international help of the Soviet Country enabled the leaders of the Komsomol press of Lithuania to get more experience, to prepare people for the underground work, to make them stronger both in politics and theory.